Tržno komuniciranje v konkurenčnem okolju - nujnost integriranega pristopa - Mumel, Damijan (Teorija in praksa, 1998)
The contents and objectives of the paper cover three areas: (1) survey of changes in marketing communications mix resulting from development of new communication tools (2) survey of integrated marketing communication which developed as a result of nonharmonized communication within organizations in competitive environment, and (3) suitability of implementation of the concept of integrated marketing communication in Slovenia.
Keywords: marketing; trženje; konkurenca; integrirano komuniciranje; tržno komuniciranje